Severe mitral regurgitation causing unilateral pulmonary edema: A case report. Issue 2 (August 2022) - Bekiaridou, Alexandra; Kartas, Anastasios; Moysidis, Dimitrios V.; Papazoglou, Andreas S.; Patsiou, Vasiliki; Baroutidou, Amalia; Kamperidis, Vasileios; Giannakoulas, George
Abstract: This is a case of a 70-year-old male patient with a history of degenerative mitral valve disease who presented to the emergency department with progressively worsening dyspnea. Prominent findings were rapid atrial fibrillation and unilateral pulmonary edema. Transthoracic and transesophageal echocardiography revealed chordal rupture-related severe-eccentric mitral regurgitation. The patient underwent surgical mitral valve repair. Learning objectives: To acknowledge that the clinical presentation may not be as dramatic when acute mitral regurgitation (MR) is superimposed on chronic MR, due to the increased left atrium compliance To bear in mind that eccentric jets of severe MR can cause unilateral pulmonary infiltrates, mimicking a primary pulmonary process To remind that rapid atrial fibrillation might be the result rather than the cause of acute cardiac decompensation.